PERAN GURU DALAM PENERAPAN METODE BERCERITA PADA ANAK USIA DINI DI PAUD SANDAT KUNING MATARAM - Anggreni, Ni Luh Eka Yuli (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Storytelling is one of the most interesting learning methods to be applied in a lesson in PAUD. The purpose of this research is to explain the teacher's role in the application of storytelling methods and to develop, improve the creativity and ability of teachers in the application of storytelling methods applied to early childhood education at PAUD Sandat Kuning Mataram. The formulation of the problem in this research is about: 1) What is the role of the teacher in the application of the storytelling method at PAUD Sandat Kuning Mataram. 2) What are the teacher's obstacles in implementing the storytelling method at PAUD Sandat Kuning Mataram. This research was solved using descriptive qualitative method by applying an experimental approach and the problems studied were using two theories, namely the theory of motivation and the theory of Behaviorism. The results of the study show that the role of teachers in the application of storytelling methods at PAUD Sandat Kuning Mataram can be seen starting from: 1) Teachers as learning managers, 2) Teachers as motivators, 3) Teachers as assessors. Teachers' Obstacles in Applying Storytelling Methods at PAUD Sandat Kuning Mataram, including: 1). The lack of learning media, the lack of learning media in question, one example is the unavailability of story books which is one of the obstacles in increasing students' learning motivation so that learning objectives cannot be achieved optimally. 2) Lack of concentration and enthusiasm of students in learning to tell stories. 3) Lack of number of educators, it also has a very big influence, because educating early childhood is something that requires more time and patience, because at this time they are actively-active and do require supervision and special ways to provide education. learning. Keywords: Teacher's Role, Storytelling Method, Early Childhood.